Biology simulations - Pelangi Multimedia Technologies Sdn. Bhd.; Penerbitan Pelangi Sdn. Bhd. (Selangor : Pelangi Multimedia Technologies Sdn. Bhd. : Penerbitan Pelangi Sdn. Bhd. (distributor), 2006)
This cd-rom consists of 3D models that are used extensively, the experiment parameters that can be set and the results that will shown in real time. This cd-rom consists of 65 simulations and is divided into 9 chapters
PTSL : volume 1 ; volume 2
System requirements : Windows 98/ME/2000/XP
Keywords: Biology -- Study and teaching -- Simulation methods; Biology -- Study and teaching (Secondary); Biology